Discriminating between Anxious and Non-Anxious Subjects Using the Toronto Hospital Alertness Test - Shapiro, Colin; Truffaut, Lucie; Matharan, Sophie; Olivier, Valérie (Frontiers in Psychiatry, 2017)
Background: Alertness designates the internal feeling of wakefulness or arousal and is often described to be linked to the level of anxiety. An adequate level of anxiety favouring the alertness needed to deal with a faced specific situation efficiently, too much anxiety can result in failure to process information and respond appropriately. Thus it would be of interest to verify if different alertness profiles can be observed depending on anxiety level. The Toronto Hospital Alertness Test (THAT) is a test designed to measure alertness. The present survey’s aim is to verify if the THAT allows observing different alertness profile between self-described anxious and non-anxious subjects. Methods: Subjects >18 years were selected from online databases in 3 countries (Canada, USA and UK). All respondents filled in a Hospital Anxiety Depression Scale (HADS) questionnaire, and only those self-classified as anxious or non-anxious (HAD-A > 11 or HAD-A< 7 respectively) took part to the survey and were asked to complete the THAT. Results: Among 616 respondents retained in the survey, 414 were self-assessed as anxious and 202 as non-anxious. The mean THAT score for anxious and non-anxious subjects was 21.4 and 38.9, respectively. A receiving operator characteristics (ROC) curve of THAT scores indicated that a threshold score of 30 was required to achieve good sensitivity (86.7%) and specificity (88.6%), with good discriminatory power (an area under the curve [AUC] of 0.938). As age was determined to be a potential confounder, subjects were age-matched giving a ROC with an AUC of 0.931, with good sensitivity (88.5%) and specificity (89.3%), and the threshold remaining at 30. The internal reliability of THAT in anxious subjects was good (Cronbach alpha=0.84). Limitations: No independent verification of anxious or non-anxious status, or other eligibility criteria was done. Conclusions: The alertness profiles of self-defined anxious and non-anxious subjects observed on THAT are different. Based on a subject’s alertness profile, it is possible to discriminate between self-defined anxious and non-anxious, using THAT, with good specificity and sensitivity at a threshold score of 30.